TARI ALANG SUNTIANG PANGULU: TARIAN ADAT MASYARAKAT PADANG LAWEH DI MINANGKABAU(TANTANGAN DAN PROBLEMATIKA) - Wahida Wahyuni; Yusfil Yusfil; Suharti Suharti (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT The traditional dances in Minangkabau are known as folk plays (pamenan) which are open, collective, and played as a medium to live the philosophy of their lives. This is illustrated in the dance of AlangSuntiangPangulu living in the community of Padang LawehAgam regency, West Sumatera Province. This dance is a traditional dance that serves to convey the messages of a leader’s leadership in leading his people. Nevertheless, the movements manifested come from the environment of the place of growth and each have the meaning in accordance to the leadership of the Penghulu. Ethnochoreologically, it emphasizes that the dance of AlangSuntiangPangulu is a cultural product that serves as a communication medium in the social life and of course contains ethnic values in it. As a traditional dance it cannot be learned by any person unless there is a family relationship or one. This is a problematic and challenging in the creative industry of Performing Arts.